ANALISIS FAKTOR PERBEDAAN HASIL BELAJAR KELAS XI IPS PELAJARAN EKONOMI SMA ASISI PONTIANAK - Utami, Hana Syarifah; Halidjah, Siti; Sabri, Tahmid (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractIn learning to write poetry in class V Public Elementary School 66 Pontianakthere are still many students who have not been able to write poetry well. This needs to be overcome by updating learning, either through the use of media or learning models. One that has been tested and proven to support students' skills in writing poetry is to apply an outdoor learning model. Based on the analysis of the situation, the problem in this study is